Formation of d-wave superconducting order in a randomly doped lattice: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Loktev, V. M.; Pogorelov, Yu. G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
We consider the interplay between superconducting coupling and dopant impurity scattering ofcharge carriers in planar square lattice systems and examine the physical conditions (doping level,temperature, local symmetry of coupling and scattering potentials) necessary in this model system to obtain a d-wave superconducting order, like that observed in real doped cuprate HTSC materials. Using the Lifshitz model for the disorder introduced into system by dopants, we analyze also the nonuniform structure of such a d-wave parameter, including both its magnitude and phase variation. The resultsindicate that d-wave superconductivity becomes possible in a doped metal until it is destroyed at too high doping levels.